Cost-effectiveness of Hepatitis B Virus Infection Screening and Treatment or Vaccination in 6 High-risk Populations in the United States. (26th December 2018) - Chahal, Harinder S; Peters, Marion G; Harris, Aaron M; McCabe, Devon; Volberding, Paul; Kahn, James G
Abstract: Background: Two million individuals with chronic hepatitis B (CHB) in the United States are at risk for premature death due to liver cancer and cirrhosis. CHB can be prevented by vaccination and controlled with treatment. Methods: We created a lifetime Markov model to estimate the cost-effectiveness of strategies to prevent or treat CHB in 6 high-risk populations: foreign-born Asian/Pacific Islanders (API), Africa-born blacks (AbB), incarcerated, refugees, persons who inject drugs (PWID), and men who have sex with men (MSM). We studied 3 strategies: (a) screen for HBV infection and treat infected ("treatment only"), (b) screen for HBV susceptibility and vaccinate susceptible ("vaccination only"), and (c) screen for both and follow-up appropriately ("inclusive"). Outcomes were expressed in incremental cost-effectiveness ratios (ICERs), clinical outcomes, and new infections. Results: Vaccination-only and treatment-only strategies had ICERs of $6000–$21 000 per quality-adjusted life-year (QALY) gained, respectively. The inclusive strategy added minimal cost with substantial clinical benefit, with the following costs per QALY gained vs no intervention: incarcerated $3203, PWID $8514, MSM $10 954, AbB $17 089, refugees $17 432, and API $18 009. Clinical complications dropped in the short/intermediate (1%–25%) and long (0.4%–16%) term. Findings were sensitive to age, discount rate, health state utility in immune or susceptible stages, progression rate to cirrhosis or inactive disease, and tenofovir cost. The probability of an inclusive program costing <$50 000 per QALY gained varied between 61% and 97% by population. Conclusions: An inclusive strategy to screen and treat or vaccinate is cost-effective in reducing the burden of hepatitis B virus among all 6 high-risk, high-prevalence populations.